(3GdEOGQI GdCeQjcjI hbVGjG GdfXGe GdOhdj GdeYGUQs - (3eMeO(B, (3HhHhTs ((3YeGf(B:s (3ecJHI OLdI ddWHGYI hGdfTQ hGdJhRjY(B,s, 2022)
(3jgOa gPG GdcJGH Edi JMdjd Yejb dOhQ GdhdGjGJ GdeJMOI GdCeQjcjI aj EOGQI GdCReGJ GdOhdjI hGdeMdjI, hJCKjQ SjGSJgG GdNGQLjI Ydi GdfXGe GdOhdj(B.(3GdaUhd GdChdi hGdKGfjI hGdKGdKI(B: (3JQcR gPg GdaUhd Ydi JMdjd GdHfjI GdeDSSjI GdCeQjcjI GdecdaI HEOGQI GdCReGJ, hcjajI JaGYd GdEOGQI GdCeQjcjI eY GdbVGjG GdNGQLjI hGdefXeGJ GdOhdjI(B. (3jJe JSdjW GdVhA Ydi GdBdjGJ hGdSjGSGJ GdeJHYI aj GJNGP GdbQGQGJ, hGdJMOjGJ GdJj JhGLggG GdhdGjGJ GdeJMOI aj gPG GdeLGd(B. (3GdaUd GdQGHY hGdNGeS(B: (3jfJbd GdcJGH Edi OQGSI cjajI JWHjb GdhdGjGJ GdeJMOI dfXQjGJgG aj EOGQI GdCReGJ Ydi GdeSJhi GdOhdj hGdeMdj(B. (3jJe JMdjd MGdI OQGSjI dJOHjQ CReI eYjfI, hJbjje eOi fLGM Ch aTd GdSjGSGJ GdeJHYI(B. (3ceG jJe HMK GdJOGYjGJ GdOGNdjI hGdNGQLjI dgPg GdSjGSGJ Ydi GdhdGjGJ GdeJMOI faSgG(B.(3GdaUd GdSGOS hGdSGHY(B: (3jJfGhd gPGf GdaUdGf GdJMOjGJ GdJj JhGLg GdbjGOI GdCeQjcjI ddfXGe GdOhdj aj Xd GdJZjQGJ GdYGdejI GdeJSGQYI(B. (3jJe JMdjd CReI chQhfG cMGdI OQGSjI dJbjje cjajI GSJLGHI GdhdGjGJ GdeJMOI dgPg GdCReI, hJCKjQgG Ydi GdOHdheGSjI GdCeQjcjI hGdfXGe GdOhdj(B.(3GdaUd GdKGef(B: (3jNJJe GdcJGH HJMdjd eSJbHd GdSjGSI GdNGQLjI GdCeQjcjI aj Xd GdEOGQI GdLOjOI HYO JQGeH(B. (3jJe WQM JSGDdGJ Mhd GdJhLgGJ GdeMJedI ddSjGSI GdNGQLjI GdCeQjcjI, hJCKjQgG Ydi GdYdGbGJ GdOhdjI(B.(3HTcd YGe, jgOa gPG GdcJGH Edi JbOje QDjI TGedI dOhQ GdhdGjGJ GdeJMOI aj YGde eJZjQ, hJbjje eOi aGYdjI SjGSGJgG aj EOGQI GdCReGJ hMaX GdGSJbQGQ GdOhdj(B. s
(3GdeQGLY U(B.289s
Keywords: (3GdhdGjGJ GdeJMOI (B- (3YdGbGJ NGQLjI (B- 2017-2021s; (3GdSjGSI GdNGQLjI (B- (3GdhdGjGJ GdeJMOI GdCeQjcjIs